2019
DOI: 10.1016/j.jtcvs.2018.11.124
|View full text |Cite
|
Sign up to set email alerts
|

Initial results of pulmonary resection after neoadjuvant nivolumab in patients with resectable non–small cell lung cancer

Abstract: Objective: We conducted a phase I trial of neoadjuvant nivolumab, a monoclonal antibody to the programmed cell death protein 1 checkpoint receptor, in patients with resectable non-small cell lung cancer. We analyzed perioperative outcomes to assess the safety of this strategy.Methods: Patients with untreated stage I-IIIA non-small cell lung cancer underwent neoadjuvant therapy with 2 cycles of nivolumab (3 mg/kg), 4 and 2 weeks before resection. Patients underwent invasive mediastinal staging as indicated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
214
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(245 citation statements)
references
References 30 publications
24
214
5
2
Order By: Relevance
“…However, the benefit of this strategy in patients with resectable NSCLC remains unknown. Previous studies have shown that neoadjuvant therapy may cause hilar inflammation and fibrosis, which will increase surgical difficulties. For patients with resectable NSCLC who need sleeve resection, it may be better to perform surgical treatment followed by adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefit of this strategy in patients with resectable NSCLC remains unknown. Previous studies have shown that neoadjuvant therapy may cause hilar inflammation and fibrosis, which will increase surgical difficulties. For patients with resectable NSCLC who need sleeve resection, it may be better to perform surgical treatment followed by adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…22 Neoadjuvant checkpoint inhibitor clinical trials have since become commonplace in academic centers, and thoracic surgeons are more frequently performing operations in patients after immunotherapy. One of the first articles on the safety of lobectomy after checkpoint inhibition is by Bott and colleagues, 23 published in the Journal in December of 2018, and is expected to prove a valuable resource for practicing thoracic surgeons. In the year ahead, we can expect to see the results of the ongoing investigation of checkpoint blockade for early-stage NSCLC brought to the readership of the Journal through Original Research and Feature Expert Opinion articles.…”
Section: Looking Forward: Checkpoint Blockade In Non-small Cell Lung mentioning
confidence: 99%
“…The trial demonstrated an unprecedented 45% major pathologic response (MPR) rate after only 2 cycles of nivolumab before surgery. Surgical outcomes of this trial were published by Bott and colleagues, 8 who highlighted that there were no delays in resections, morbidity outcomes were comparable to those of neoadjuvant chemotherapy regimens, and, perhaps most importantly, a 54% (7/13) conversion rate was seen from either a video-assisted thoracoscopic surgery or a robotic-assisted thoracoscopic surgery initial approach to thoracotomy in response to an ''inflamed hilum.'' Communications among thoracic surgeons about anecdotal cases of inflammation after immunotherapy suggest that operating on patients in this setting is perhaps technically more challenging than operating primarily on early lung cancer.…”
mentioning
confidence: 99%
“…Importantly, though, perioperative outcomes are not negatively affected by this slightly increased technical challenge. 8 The inflammatory reaction to ICIs appears to be idiosyncratic, and we currently do not have biomarkers that can predict intraoperative inflammation before surgical inspection of the pleural space.…”
mentioning
confidence: 99%